Corruption and Foreign Direct Investment (FDI) in ASEAN-5: A Panel Evidence - Bakri Abdul Karim; Zulkefly Abdul Karim; Mohamad Naufal Nasharuddin (Institute for Economic and Social Research, 2018)
This paper examines the effects of corruption on the inﬂow of FDI in ASEAN-5 countries by controlling twomacroeconomic variables namely Gross Domestic Product (GDP) and inﬂation. Using a static panel dataestimation, the results show the signiﬁcant relationship between corruption and Gross Domestic Product(GDP) on the inﬂow of FDI in ASEAN-5. This results indicate that less corrupted countries and largermarket size would attract more FDI inﬂows. The policy implications from this study suggests that ASEAN-5governments need to have concerted and continues efforts in improving the integrity and credibility of theiradministration and transactions. In addition, maintaining their sustainable of economic growth is also crucial as a full factor in attracting more FDI inﬂows in future.